EU diplomacy and the Israeli-Arab conflict, 1967-2019 - Persson, Anders, 1982- (Edinburgh University Press, 2020)
Based exclusively on primary sources, this study offers an up-to-date overview of EU's involvement in the Israeli-Arab conflict since 1967.